Women’s Position on the Hindu Law in the Vivaha Samskara System - Chandra Sagaran; Made Aripta Wibawa (Sociological Jurisprudence Journal, 2018)
There are assumptions and interpretations which consider marriage as a part of the Panca Yajna, especially the Manusa Yajna, as Pawiwahan (marriage) involving human affairs (individual). Pawiwahan is included in the tiered samskara (rites of passages in one’s life and purification) system. The study discusses the women’s position in law of Hindu of Vivaha Samskara system. This study employs qualitative research method with normative law research design. To achieve objectives of the study, this study made use of statute approach and conceptual approach in collecting and analyzing the legal materials. The results show that women's position in the Vedas is highly respected although the law has always undergone modifications and change of material. In Hindu marriage system, sanctions are to be enforced for: impregnating biological children, having sexual intercourse in the temple, sexually assaulting an underage daughter (kanya wighna), sexually assaulting their own daughter (swaputribhajana), having sexual intercourse with biological mother (mater bhajana), killing women (yuwati wadha), abortion (bruhanahatya), and sexually assaulting underage children. All of these are considered great sins (Ati Pataka) according to Slokantara 15-17, whose sanctions are not included in the awig-awig adat (traditional custom rules).